2017
DOI: 10.1515/agri-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Current State and Development of Land Degradation Processes Based on Soil Monitoring in Slovakia

Abstract: Current state and development of land degradation processes based on soil monitoring system in Slovakia is evaluated in this contribution. Soil monitoring system in Slovakia is consistently running since 1993 year in 5-years repetitions. Soil monitoring network in Slovakia is constructed using ecological principle, taking into account all main soil types and subtypes, soil organic matter, climatic regions, emission regions, polluted and non-polluted regions as well as various land use. The result of soil monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…This difference is probably related to the long-term and intense fertilization of these soils with Cd-bearing phosphorus fertilizers and other biosolid amendments (McLaughlin et al 1999), as any other sources of contamination with Cd are absent in the chernozemic region of SW Poland (Kabala et al 2015). Nevertheless, the median values found in the present study for Mn and Cd are considered a reliable geochemical baseline, at least on a Central European scale (Kabata-Pendias 2011; Kobza et al 2017; Komárek et al 2008; Rékási and Filep 2012; Salminen and Tarvainen 1997; Spahić et al 2018).…”
Section: Discussionmentioning
confidence: 53%
“…This difference is probably related to the long-term and intense fertilization of these soils with Cd-bearing phosphorus fertilizers and other biosolid amendments (McLaughlin et al 1999), as any other sources of contamination with Cd are absent in the chernozemic region of SW Poland (Kabala et al 2015). Nevertheless, the median values found in the present study for Mn and Cd are considered a reliable geochemical baseline, at least on a Central European scale (Kabata-Pendias 2011; Kobza et al 2017; Komárek et al 2008; Rékási and Filep 2012; Salminen and Tarvainen 1997; Spahić et al 2018).…”
Section: Discussionmentioning
confidence: 53%
“…The agricultural land of the Slovak Republic covers 2, 432, 979 hectares and soil organic carbon content of arable land is typically unsatisfactory. In several most productive areas the soil organic carbon content has decreased to low levels (Kobza et al, 2017). The recently observed decrease in SOM is a result of intensifying soil degradation processes related to human activity such as incorrect and intensive soil management practices.…”
Section: Introductionmentioning
confidence: 99%
“…The average content of C was determined in Chernozems, Luvisols, Mollic Fluvisols, Albeluvisols, Rendzic Leptosols, Fluvisols and Cambisols 1.55, 1.24, 2.34, 1.70, 2.87, 1.60 and 2.48%, respectively [Linkeš et al 1997]. The content of organic C in Slovakian soils is not sufficient and the latest results of the partial monitoring -Soil (the previous 5 years) showed that the content of C has increased slightly in the soil types such as: Fluvisols, Mollic Fluvisols, Chernozems, Rendzic Leptosols and Podzols, on the contrary, it has decreased in Cutanic Luvisols, Haplic Planosols and Regosols [Kobza et al, 2017]. As the decline of organic carbon in soils can result in the decrease of soil quality, it was essential to fix the limiting (threshold) values of C content in the particular regions.…”
Section: Introductionmentioning
confidence: 99%